Farewell to Welfare: An End to Citizenship as We Know It - Pinzani, Alessandro (SocietàMutamentoPolitica, 2016)
The crisis of the welfare state has been a widely discussed topic since at least the 1970s both in the social sciences and in political debate. It is not my intention to readdress it or to analyze the many diagnoses of the meaning and scope of the crisis: there is a huge amount of literature on this and I do not aim to add another contribution. Rather I would like to investigate the reasons that led to the wide acceptance among the public in Western Europe (and probably elsewhere) of the dismantling of certain features of the welfare state. To this end, I shall focus on the discourses that justified this process and that have provided a major shift in the political vocabulary from the grammar of (social) rights to the grammar of performance and (state) services. In other words, I shall concentrate on the paradigm change from a Keynesian model of welfare state to a ‘neoliberal’ model of personal responsibility. This change of paradigm threatens the very idea of citizenship as we have known it for centuries.